2013
DOI: 10.1017/s0022149x13000369
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of intermediate forms of Fasciola hepatica and F. gigantica in buffaloes from Central Punjab, Pakistan

Abstract: Fascioliasis is an important food-borne parasitic disease caused by the two trematode species, Fasciola hepatica and Fasciola gigantica. The phenotypic features of fasciolid adults and eggs infecting buffaloes inhabiting the Central Punjab area, Pakistan, have been studied to characterize fasciolid populations involved. Morphometric analyses were made with a computer image analysis system (CIAS) applied on the basis of standardized measurements. Since it is the first study of this kind undertaken in Pakistan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
(80 reference statements)
1
20
1
Order By: Relevance
“…Further, in a more recent morphometric analysis of Fasciola isolates from buffalo originating from the districts of Punjab province, similar to some of those included in this study, Afshan et al (2013) reported F. hepatica and F. gigantica, along with intermediates of both species. The difference between the results here and those of previous studies may be due to the fact that the previous identifications were based purely on morphological analysis.…”
Section: Fasciola Gigantica In Ruminants From Pakistansupporting
confidence: 51%
“…Further, in a more recent morphometric analysis of Fasciola isolates from buffalo originating from the districts of Punjab province, similar to some of those included in this study, Afshan et al (2013) reported F. hepatica and F. gigantica, along with intermediates of both species. The difference between the results here and those of previous studies may be due to the fact that the previous identifications were based purely on morphological analysis.…”
Section: Fasciola Gigantica In Ruminants From Pakistansupporting
confidence: 51%
“…The remaining variables (PCII, Y axis) were all significantly correlated with the first principal component (PCI, X axis), contributing 58% to overall variations. The PCI could therefore be accepted as a general indicator of size (Afshan et al 2013), so that the resulting factor maps (Fig. 3) can clearly illustrate global size differences in the populations analysed.…”
Section: Discussionmentioning
confidence: 99%
“…A -Chakaria; B -Bhola Sadar; C -Rangamati Sadar; D -Sylhet Sadar; E -Patnitola; F -Shapahar; G -Naogaon Sadar; H -Ishwardi; I -Ishwarganj; J -Lalmonirhat Sadar; K -Mymensingh Sadar; L -Dhunat; M -Shailkupa; N -Jhenaidah Sadar uration in the biliary duct system up to the onset of egg production. Consequently, to avoid the influence of age and growth on the trematode comparison, morphological variation is quantified by geometrical morphometrics (Rohlf and Marcus, 1993), a technique offering an estimate of size by which different axes of growth are integrated into a single variable (Afshan et al 2013). The estimate of size is contained in a single variable reflecting variation in many directions, as many as there are landmarks under study, and shape is defined as their relative positions after correction for size, position and orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environments in which water buffalo are kept are well suited to the water and mud snails that act as intermediate hosts for a range of Fasciolidae, Paramphistomatidae, Dicrocoeliidae and Schistosomatidae trematode parasites of the liver, forestomach, intestinal tract and blood, causing disease and production loss. Immature and adult parasites of the Fasciolidae (Afshan et al, 2013;Amor et al, 2011;Shahzad W, 2012;Shoriki et al, 2014) and Paramphistomatidae families (Hanna et al, 1988;Ichikawa et al, 2013;Khan et al, 1990;Mazahery et al, 1994) are common in the liver parenchyma and bile ducts of slaughtered buffalo kept throughout subtropical regions. In addition, the Dicrocoeliidae family parasites which require a land snail first intermediate host, are occasionally reported in the livers of buffalo in subtropical regions, for example in Iran and India (Eduardo, 1985;Gorjipoor et al, 2015;Jithendran and Bhat, 1996).…”
Section: Introductionmentioning
confidence: 99%